Global environmental issues - Harris, Frances (Hoboken, NJ : John Wiley & Sons, 2011)
This new edition of a popular book looks at global environmental problems as complex issues with a network of causes. In addition to discussing the main biophysical causes, the book highlights the environmental and social impact of scientific developments, and examines how socio-economic and political factors affect the use of land and resources.
Includes bibliographical references and index.
Keywords: Environmental sciences